A teoria holística da atividade e a constituição do papel docente na formação inicial do educador linguístico - Camillo, Leila Bom (2017)
This research aims to objective accompany discursively the construction of the role of the linguistic educator in an internship context, as from a supervised listening based on the Holistic Theory of Activity (THA). It how as a theoretical basis the new version of the THA, version 4.3, which adds to the attribution factors, the concept of secure basis for supervising the stage in Letters / Portuguese, in an affective-identificatory dimension and the concept of Co-Responsible Professional Development (DPC) accomplished in the didactic alliance between school and university. The supervised listening, like a safe base, now has as committed to welcoming, guiding and encouraging the intern at the beginning of teaching. Already the didactic alliance, constituted by the academic, supervisor of internship and teacher regent of the school, establishes a didactic contract in which is discussed the conflicts of the profession coming from the surroundings of the social system. The methodology has a qualitative approach and it is by action research with a single case study, a intern in probationary time in Elementary School. The instruments of qualitative analysis are the enunciations of four discursive events in two contexts: two in the academic guidelines and two in the didactic alliance. The analysis of the data was made from a discursive analysis and the indiciary paradigm. The discursive marks found were the verbs 'to be', in the present temporality, marking the constituent experiences of the intern throughout the process. To capture the construction of identity, a study was carried out of teacher making, teacher thinking and teacher perception, locating them in the factors of the holistic framework. Thus, the factors of the Holistic Theory of Activity served as reference in the analysis of the moments on what the intern approached the more integrated role of the linguistic educator and the more fragmented role. It was possible to observe the functionality of the THA in supervising the internship, the viability of the didactic alliance in the initial formation and the dialectical process of the constitutive movement of the intern in relation to the fragmentation and integrality of the teaching role. The fragmentation of the role appeared in the discourses of teacher thinking in pre-established concepts, in the discourses of teacher doing with actions without theoretical reflection, and in the teacher feeling, in discourses based on disorganized emotions. This research portrayed the Holistic Theory of Activity as a safe basis of support and zeal for the social system of the linguistic educator and showed that the supervised listening is qualified from a continuous reflective work.